2020
DOI: 10.3390/pharmaceutics12121247
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Medicine in Times of COVID-19: How Radiopharmaceuticals Could Help to Fight the Current and Future Pandemics

Abstract: The emergence and global spread of COVID-19, an infectious disease caused by the novel coronavirus SARS-CoV-2, has resulted in a continuing pandemic threat to global health. Nuclear medicine techniques can be used for functional imaging of (patho)physiological processes at the cellular or molecular level and for treatment approaches based on targeted delivery of therapeutic radionuclides. Ongoing development of radiolabeling methods has significantly improved the accessibility of radiopharmaceuticals for in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…Due to their critical role in processing and generating 16 non-structural proteins involved in SARS-CoV-2 replication, the SARS-CoV-2 proteases, including Mpro and PLpro, are other attractive targets for COVID-19 treatment. To date, several novels or repurposed drugs have been recognized that effectively interact with one or both the viral proteases, thereby inhibiting the processing of the replicase polyproteins and assembly of the viral transcription or replication complex (Neumaier et al 2020 ). They can divide into two groups: (1) peptides that mimic part of the substrate of the proteases and (2) different small molecule drugs.…”
Section: Potential Strategies and Therapeutic Agents For Covid-19 Tre...mentioning
confidence: 99%
“…Due to their critical role in processing and generating 16 non-structural proteins involved in SARS-CoV-2 replication, the SARS-CoV-2 proteases, including Mpro and PLpro, are other attractive targets for COVID-19 treatment. To date, several novels or repurposed drugs have been recognized that effectively interact with one or both the viral proteases, thereby inhibiting the processing of the replicase polyproteins and assembly of the viral transcription or replication complex (Neumaier et al 2020 ). They can divide into two groups: (1) peptides that mimic part of the substrate of the proteases and (2) different small molecule drugs.…”
Section: Potential Strategies and Therapeutic Agents For Covid-19 Tre...mentioning
confidence: 99%
“…The in vivo biodistribution of the tracer is then tracked by detecting the antiparallel γ-quants produced after the decay of the radionuclide and annihilation of the emitted positrons with electrons in surrounding tissues. Adapted from [ 45 ] (CC BY 4.0).…”
Section: Figurementioning
confidence: 99%
“… 59 , 60 Furthermore, one study has shown how radionuclides can be used to target therapy to SARS-CoV-2 virion or infected cells. 61 …”
Section: Novel Applications Of Imagingmentioning
confidence: 99%